2011
DOI: 10.1200/jco.2010.32.9110
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib Efficacy in Renal Cell Carcinoma: Evidence for Predictive Genetic Markers in Angiogenesis-Related and Exposure-Related Genes

Abstract: Germline variants in angiogenesis- and exposure-related genes may predict treatment response to pazopanib monotherapy in patients with RCC. If validated, these markers may explain why certain patients fail antiangiogenesis therapy and they may support the use of alternative strategies to circumvent this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(117 citation statements)
references
References 32 publications
4
113
0
Order By: Relevance
“…With regard to pazopanib, SNPs in UGT1A1, CYP1A2, and HFE were associated with either bilirubin levels or ALT levels, and SNPs in IL8, HIF1A, NR1I2, and VEGFA were associated with efficacy outcomes on pazopanib. The association of rs1126647 in IL8 with OS was confirmed in two independent data sets including patients treated with either sunitinib or pazopanib [40,42]. Sorafenib toxicity and efficacy were related to genetic polymorphisms in ABCC2, HLA-A, and the only large study (n > 300) available on sorafenib treatment showed rs2071559 in VEGF-R2 was related to efficacy.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…With regard to pazopanib, SNPs in UGT1A1, CYP1A2, and HFE were associated with either bilirubin levels or ALT levels, and SNPs in IL8, HIF1A, NR1I2, and VEGFA were associated with efficacy outcomes on pazopanib. The association of rs1126647 in IL8 with OS was confirmed in two independent data sets including patients treated with either sunitinib or pazopanib [40,42]. Sorafenib toxicity and efficacy were related to genetic polymorphisms in ABCC2, HLA-A, and the only large study (n > 300) available on sorafenib treatment showed rs2071559 in VEGF-R2 was related to efficacy.…”
Section: Discussionmentioning
confidence: 72%
“…A worse PFS and response rate were observed for AG carriers of rs11549467 in HIF1A compared to wild-type GG. A reduced response rate was also observed for TT carriers of rs3814055 in NR1I2 compared to wild-type CC and for wildtype CC of rs833061 in VEGFA compared to TT genotypes [40].…”
Section: Pharmacogenetics To Predict Pazopanib Efficacymentioning
confidence: 78%
See 2 more Smart Citations
“…Xu C.V. has shown the genetic association of HIF-1α with response to pazopanib monotherapy [37]. So, search of molecular markers predicting the effectiveness of targeted therapy is actually for modern oncology.…”
Section: Introductionmentioning
confidence: 99%